Corrosion of nickel-base alloys in primary medium of pressurized water reactors: New insights on the oxide growth mechanisms and kinetic modelling. (January 2016) - Marchetti, Loïc; Perrin, Stéphane; Jambon, Fanny; Pijolat, Michèle
Highlights: Review of results related to Ni-base alloy oxidation in PWR primary medium. Proposition of an oxide growth mechanism. Development of a kinetic model linking alloy surface defect density to oxidation. Comparison of modelled kinetics and experimental data for oxide growth and cation release. Abstract: The generalised corrosion of Ni-base alloys exposed to pressurized water reactors primary coolant leads both to the growth of a protective oxide scale and to the release of cations. Based on experimental results previously published, a mechanistic description of this phenomenon is proposed. Then, from a simplified view of theses mechanisms, a kinetic model is proposed, focusing on the link between the alloy subsurface defects density and the shape of oxidation kinetic curves. Comparing calculated curves and experimental data shows this first approach is promising. Nevertheless a better knowledge of some kinetic parameters is necessary to improve the model.